Interactive visualization for curatorial analysis of large digital collection. (April 2014) - Xu, Weijia; Esteva, Maria; Jain, Suyog D; Jain, Varun
To make decisions about the long-term preservation of and access to large digital collections, digital curators use information such as the collections' digital object types, their contents and preservation risks, and how they are organized. To date, the process of analyzing a collection—from data gathering to exploratory analysis and final conclusions—has largely been conducted using linear review and pen and paper methods. To help curators analyze large-scale digital collections, we developed an interactive visual analytics application. We have put methods in place to summarize large and diverse information about the collection and to present it as integrated views. Multiple views can be linked or unlinked on demand to enable curators to identify trends and particularities at different levels of detail and to compare and contrast views. We describe two analysis workflows to illustrate how the application can be used to triage digital collections and facilitate collection management decision making and to provide access. After conducting a focus group study with domain specialists, we introduced features to address their concerns and needs.